Outcomes Of Microincision Pars Plana Vitrectomy In Rhegmatogenous Retinal Detachment - Subedi, Santosh; Thapa, Raba; Pradhan, Eli; Bajiyama, Sanyam; Sharma, Sanjita; Duwal, Sushma; Poudel, Manish; Poudyal, Govinda (Journal of Nepal Health Research Council, 2023)
Background: With the technological advances, microincision pars plana vitrectomy is commonly used method for primary treatment of eyes with rhegmatogenous retinal detachment. Objective of this study is to evaluate anatomical and visual outcomes of microincision pars plana vitrectomy in eyes with rhegmatogenous retinal detachment.Methods: This was a hospital based prospective observational study done in Tilganga Institute of Ophthalmology, Kathmandu, Nepal. All consecutive cases of rhegmatogenous retinal detachment who underwent primary microincision pars plana vitrectomy from October 2020 to March 2021 were included in the study. Patients were evaluated at baseline, postoperative day 1, 1 week, 6 weeks and 3 months. Outcome measures evaluated were anatomical results, visual outcomes and complications of the surgery.Results: Forty-nine eyes with rhegmatogenous retinal detachment treated with primary microincision pars plana vitrectomy with minimum follow up of at least 3 months were evaluated. Anatomical success was achieved in 91.8% of cases (45/49). Baseline mean best corrected visual acuity was logMAR 1.63±0.88 and median best corrected visual acuity was 2.00 (range 0.00 to 2.70) while at 3 months follow up mean best corrected visual acuity was logMAR 1.22±0.66 and median BCVA was 1.00 ( range 0.00 to 2.70). There was significant improvement in median BCVA ( p= 0.005). There were no cases of postoperative hypotony and endophthalmitis. Other complications were also minimal such as silicon oil in anterior chamber in 1 eye, epiretinal membrane in 3 eyes and macular hole in 2 eyes.Conclusions: Microincision pars plana vitrectomy is an effective surgical method of primary treatment for rhegmatogenous retinal detachment with good anatomical and visual outcomes with minimal complications.Keywords: PPV; RRD; visual outcome